Expert validation of a teamwork assessment rubric: A modified Delphi study. (January 2016) - Parratt, Jenny A.; Fahy, Kathleen M.; Hutchinson, Marie; Lohmann, Gui; Hastie, Carolyn R.; Chaseling, Marilyn; O'Brien, Kylie
Summary: Background: Teamwork is a 'soft skill' employability competence desired by employers. Poor teamwork skills in healthcare have an impact on adverse outcomes. Teamwork skills are rarely the focus of teaching and assessment in undergraduate courses. The TeamUP Rubric is a tool used to teach and evaluate undergraduate students' teamwork skills. Students also use the rubric to give anonymised peer feedback during team-based academic assignments. The rubric's five domains focus on planning, environment, facilitation, conflict management and individual contribution; each domain is grounded in relevant theory. Students earn marks for their teamwork skills; validity of the assessment rubric is critical. Question: To what extent do experts agree that the TeamUP Rubric is a valid assessment of 'teamwork skills'? Design: Modified Delphi technique incorporating Feminist Collaborative Conversations. Participants: A heterogeneous panel of 35 professionals with recognised expertise in communications and/or teamwork. Methods: Three Delphi rounds using a survey that included the rubric were conducted either face-to-face, by telephone or online. Quantitative analysis yielded item content validity indices (I-CVI); minimum consensus was pre-set at 70%. An average of the I-CVI also yielded sub-scale (domain) (D-CVI/Ave) and scale content validity indices (S-CVI/Ave). After each Delphi round, qualitative data were analysed and interpreted; Feminist Collaborative Conversations by the research team aimed to clarify and confirm consensus about the wording of items on the rubric. Results: Consensus (at 70%) was obtained for all but one behavioural descriptor of the rubric. We modified that descriptor to address expert concerns. The TeamUP Rubric (Version 4) can be considered to be well validated at that level of consensus. The final rubric reflects underpinning theory, with no areas of conceptual overlap between rubric domains. Conclusion: The final TeamUP Rubric arising from this study validly measures individual student teamwork skills and can be used with confidence in the university setting. Highlights: 'TeamUP' supports university students use of effective teamwork skills The theoretically grounded TeamUP Rubric defines and describes teamwork skills We use the TeamUP Rubric to teach and assess students doing team-based assignments Professionals with teamwork expertise have contributed to rubric validation The TeamUP Rubric is a well-validated measure of tertiary student teamwork skills